Overall in vitro, in vivo, and in silico evaluation of Olea europaea and Ficus carica leaf extracts for antimicrobial activity against multidrug-resistant pathogens - Aloriby, Mahmoud; Elkawafi, Mohamed; Aldrsy, Salem; Sweker, Mohamed; Elabdeli, Hadeel; Elbarghathi, Aisha; Benhasouna, Ahmed; El-Awamie, Madiha; Elsharif, Nariman; Alqabbasi, Omar; Alshalmani, Salmin; Algazal, Rabiea; et al. (Frontiers in Microbiology, 2025)
IntroductionAntimicrobial resistance (AMR) represents a critical global health issue, prompting the urgent exploration of alternative plant-derived antimicrobial therapies. In this context, the present study evaluates the therapeutic efficacy and safety profiles of Olea europaea and Ficus carica leaf extracts against multidrug-resistant pathogens, integrating in vitro antimicrobial assays, in vivo toxicity assessments, and in silico modeling approaches.MethodsLeaf extracts from O. europaea and F. carica were prepared by solvent-based maceration using methanol, acetone, and distilled water. Their antimicrobial properties were evaluated through disk and well diffusion assays to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against clinically relevant pathogens. Toxicological assessments were performed in vivo using the BALB/c mice model, including histopathological examinations, hematological profiling, and biochemical analyses. A complementary in vitro toxicogenomic screening was conducted using a cell-based reporter assay to profile nuclear receptor signaling and cellular stress responses. Furthermore, computational modeling and molecular docking were employed to predict the possible interactions of selected phytochemicals with E. coli cytochrome c peroxidase.ResultsMethanolic extracts of O. europaea exhibited potent antimicrobial activity against multidrug-resistant isolates, whereas F. carica extracts showed minimal efficacy across all experimental contexts. In silico molecular docking analyses revealed high-affinity interactions between olive-derived phenolic compounds and E. coli cytochrome c peroxidase, suggesting a plausible mechanistic basis for the observed antibacterial effects. In vivo, toxicological evaluation in BALB/c mice administered aqueous formulations of the methanolic olive extract demonstrated dose-dependent hepatic and renal histopathological alterations, accompanied by dysregulation of the immunological profiles and elevated hepatic enzyme levels. These findings were consistent with outcomes from the cell reporter assays and computational toxicology models, which indicated potential nephrotoxic and immunotoxic risks at higher concentrations.DiscussionThese findings validate the promising antimicrobial activity of O. europaea and F. carica leaf extracts against multidrug-resistant pathogens. However, further investigations on precise dosage optimization and long-term safety evaluations are essential before these extracts are implemented in clinical practice.